Histomorphometric features of hepatic toxicity caused by carbamazepine and its amelioration with vitamin E. - Basharat Ali, Asma; Younus, Nadia; Mukhtar, Sahrish; Abrar, Hina; Kazmi, Tayyaba; Faisal, Lubna (International Journal of Endorsing Health Science Research, 2021)
Background: Carbamazepine, a commonly prescribed anti-epileptic drug, is potentially hepatotoxic. This laboratory-based experimental study was designed to observe the toxicity of Carbamazepine and the ameliorative effects of Vitamin E on liver tissue. Methodology: A total of 54 rats were randomly divided into 3 groups. Group A was the control; group B was given oral Carbamazepine, and group C was given Carbamazepine with Vitamin E daily for 6 weeks. At the end of the study period, animals were sacrificed, their liver was preserved, and tissue was stained with Hematoxylin and Eosin. Results: The mean final body weights of Carbamazepine treated group B (147.27 ± 13.72 gm) and Carbamazepine + Vitamin E protected group C (164.43 ± 10.73 gm) were decreased significantly in comparison to control A (194.03 ± 14.87 gm). Mean absolute and relative liver weights were increased significantly in groups B & C as compared to group A. Histological examination of liver in group B showed disturbed architecture of hepatic lobules including congested central vein, dilated sinusoids, pyknotic nuclei, steatosis, portal vein dilatation, hemorrhages, and mononuclear infiltration in the portal triad and around the central vein. These changes were reduced in group C. Micrometry confirmed the histological findings, with a significant decrease in mean hepatic cell count and mean hepatocyte nuclear diameter of group B as compared to control group A (6.00 ± 1.41 & 5.62 ± 0.69 µm respectively), and a significant increase in mean hepatocyte diameter of group B in comparison to group A (17.44 ± 1.29 µm). Conclusion: This study showed that Carbamazepine caused hepatotoxicity while Vitamin E was helpful in its amelioration.